Penerapan Fungsi Sekunder Hukum Pidana Oleh Aparatur Penegak Hukum Dalam Hukum Pidana Ekonomi - Yoserwan Hamzah (Nagari Law Review, 2017)
Secondary function of criminal law indicates that criminal law will only be needed if other legal norms cannot protect the society. However, the reality shows that more criminal laws enacted and more criminal sanction are applied, especially in Economic Criminal Law. That phenomenon may lead to over-criminalization. The research concludes that there is no synchronization in the implementation of secondary function of criminal law both in formulation and implementation of criminal law. Therefore, there should be synchronization in implementing the secondary function of criminal law, and in turn it will support synchronization among law enforcement official.